ICT Training to Improve CLC Data Management through Nonformal Education Service Program - Entoh Tohani; Pujiyanti Fauziah; Iis Prasetya; Munifah Munifah; Dewi Sylviani (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
The COVID-19 pandemic has shifted the habit of face-to-face offline learning to online learning using Information, Communication and Technology (ICT). This happens in all education units, including the Community Learning Centre (CLC). Community learning centre, as nonformal education unit, has flexible characteristics. Nevertheless, it still has the competitiveness to provide learning according to the needs of students during the COVID-19 pandemic. Community activities are voluntary-based, where technology uses are still partial and not optimal. For this reason, community service activities through the training aim to provide knowledge about how information, communication, and technology are used in data management and learning. This community service program approach was carried out qualitatively by conducting in-depth interviews with community samples in each district of Yogyakarta. The offline activity was attended by 20 participants from CLC in Yogyakarta City. With this direct training and workshop, community managers can practice using cloud storage for data management and use online conference and presentation applications to support the creation of learning media.